2010
DOI: 10.1002/app.32356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of EVA as compatibilizer on the mechanical properties, permeability characteristics, lamellae orientation, and long period of blown films of HDPE/clay nanocomposites

Abstract: Two ethylene-vinyl acetate (EVA) resins with 19% (EVA19) and 28% (EVA28) of vinyl groups were used as compatibilizers for nanocomposites of high-density polyethylene (HDPE) and nanoclays. Two nanoclays were also used, one with a nonpolar surfactant (C15A) and another with a polar surfactant (C30B). The HDPE/ EVA19/C15A formed an intercalated structure, while the HDPE/EVA28/C30B had surfactant loss. Blown films of these compositions were produced. A two-phase morphology made of HDPE and EVA/nanoclay particles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Furthermore, SEM image of the nanocomposite containing of Cloisite 30B (Figure c, sample 8) showed smaller agglomerated particles compared to Cloisite 20A results (Figure b). These findings were similar to those by Marini et al (). SEM result (Figure d) of film incorporating an equal combination of three nanoparticles (2% of each, sample 16) showed more uniformity ​than the situation observed for Cloisite 15A and Cloisite 30B composites.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, SEM image of the nanocomposite containing of Cloisite 30B (Figure c, sample 8) showed smaller agglomerated particles compared to Cloisite 20A results (Figure b). These findings were similar to those by Marini et al (). SEM result (Figure d) of film incorporating an equal combination of three nanoparticles (2% of each, sample 16) showed more uniformity ​than the situation observed for Cloisite 15A and Cloisite 30B composites.…”
Section: Resultssupporting
confidence: 93%
“…The haze of the films can be correlated to the degree of crystallinity and is dependent mostly on the crystals sizes and morphologies . The haze of each film is shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Polymer/clay nanocomposites can be an alternative for the packaging industry because of their superior properties such as gas barrier performance, enhanced mechanical properties, and optical clarity when compared with the pure polymer or composites having conventional fillers . Clays can be efficiently exfoliated in polar polymers when the correct processing conditions are used ; however, when the polymer is a polyolefin, usually the attainment of exfoliated structures is more complicated because of the polyolefins hydrophobic character and to the lack of interactions with the hydrophilic surface of the clay. Therefore, treatment of the clays galleries must be done and, in some cases, when the interfacial interactions between the polyolefin and the organoclay are weak, a compatibilizer agent needs to be used.…”
Section: Introductionmentioning
confidence: 99%
“…Marini et al studied the compatibilisation effect of EVA for HDPE/MMT system and reported decreased tensile and barrier properties in comparison to the neat HDPE. 15 In another study to evaluate the effectiveness of EVA as compatibiliser on the oxygen permeability and the mechanical and thermal properties of LDPE/MMT system, the authors reported a significant increase in the interlayer spacing of MMT with the addition of EVA.…”
Section: Introductionmentioning
confidence: 99%